Relational and metaphysical mysticism in The Book of Saint Angela of Foligno - Stróżyński, Mateusz (Filozofia Chrześcijańska, 2019)
The article discusses the coexistence of two forms of Christian mysticism – metaphysical and relational – in The Book of Angela of Foligno. The metaphysical type, associated with the Neoplatonic philosophy, is probably inspired by The Soul’s Journey Into God by Saint Bonaventure who describes the experience of God as viewing existence or being (esse). The relational type is focused on the human and personal aspect of Jesus and the experience of love in the I-You relationship. While in many medieval mystics there is only one type of mysticism (e.g. metaphysical in Eckhart, relational in Bernard of Clairvaux), in Angela there is an interesting coexistence of both these types of experience of God.